UV-C inactivation of microorganisms in droplets on food contact surfaces using UV-C light-emitting diode devices - Sharma, Aakash; Mahmoud, Housyn; Pendyala, Brahmaiah; Balamurugan, Sampathkumar; Patras, Ankit (Frontiers in Food Science and Technology, 2023)
The main objective of this study was to investigate the effectiveness of ultraviolet light (UV-C) emitting diodes for the decontamination of stainless steel food contact surfaces. Listeria monocytogenes (ATCC 19115), Escherichia coli (ATCC 25922), and Salmonella enterica serovar Typhimurium (ATCC 700720) were chosen as challenge microorganisms. Target microorganisms were subjected to UV-C dosages of 0, 2, 4, 6, and 8 mJ cm−2 at an average fluence of 0.163 mW/cm2 using a near-collimated beam operating at 279 nm wavelength. Escherichia coli showed lower sensitivity to UV-C light compared to Salmonella Typhimurium and followed first-order kinetics. Escherichia coli and Salmonella Typhimurium were reduced by more than 3-log10 cycles at the maximum UV dosage of 12 mJ cm−2. In contrast, Listeria monocytogenes followed the Weibull model with an apparent shoulder in the initial doses. A maximum reduction of 4.4-log10 was achieved at the highest exposure level. This study showed that UV-C LED devices represent an excellent alternative for the inactivation of foodborne microorganisms in droplets. Results clearly demonstrate that UV-C LED devices can serve as an additional sanitation method to routine cleaning practices, which are commonly utilized in the food industry.